Impact of the COVID-19 epidemic on medical product imports from china from outbreak to stabilization: Monthly panel data regression and instrumental variable test - Pu, Yuanjie; Xu, Aidi; Wang, Hang; Qian, Fangbin (Frontiers in Public Health, 2023)
This study conduct regressions of panal data with OLS and test with IV, empirically examines the COVID-19 epidemic's impact on the import of medical products from China from the perspective of the importing countries, exporting country, and other trading partners, and analyzes the inter-temporal impact across different product categories. The empirical results reveal that, in importing countries, the COVID-19 epidemic increased the import of medical products from China. In China, as an exporting country, the epidemic inhibited the export of medical products; by contrast, for other trading partners, it promoted the import of medical products from China. Among them, key medical products were most affected by the epidemic, followed by general medical products and medical equipment. However, the effect was generally found to wane after the outbreak period. Additionally, we focus on how political relations shape China's medical product export pattern and how the Chinese government is using trade means to improve external relations. In the post-COVID-19 era, countries should prioritize the stability of supply chains for key medical products and actively engage in international cooperation on health governance to further combat the epidemic.